Experimental investigation on the hydrodynamic effects of heave plates used in floating offshore wind turbines. (1st January 2023) - Zhang, Lixian; Shi, Wei; Zeng, Yuxin; Michailides, Constantine; Zheng, Siming; Li, Ying
Abstract: Due to the abundant wind energy in deep water, floating offshore wind turbines (FWTs), especially for the semisubmersible FWTs, have attracted more attention these years. To reduce the heave motion of FWTs, heave plates are often attached at the bottom of the column. In this paper, experimental investigations of the hydrodynamic performance of the heave plates via the forced oscillation method are conducted. The impacts of the KC number ( KC  = 0.1–1.1), oscillation frequency ( f  = 0.4–1.43 Hz), diameter ratio- D d / D c ( D d and D c are the diameter of the heave plate and column), thickness ratio- t d / D d ( t d is the thickness of the heave plate), shapes of the heave plates, on the added mass, and damping coefficients are investigated. The results show that the added mass and damping coefficients are independent of oscillation frequencies, while the KC number influences significantly the hydrodynamic coefficients. Increase in the diameter ratios will decrease the added mass and damping coefficients. The thinner heave plates obtain larger damping coefficients. Comparison between the different shapes of the heave plates shows that the octagonal heave plate displays similar added mass and damping coefficients to the circular heave plate. However, square one obtains lower added mass coefficients compared to the other three shapes. And the hexagonal plate seems to have the highest damping force for different KC numbers. Highlights: Hydrodynamic performance of heave plates were investigated via an experimental approach. The effects of the KC numbers and oscillation frequencies on the hydrodynamic coefficients were analyzed. Diameter ratios and shapes effect of the heave plate on the hydrodynamic performance were also carried out. KC numbers have great influence on the hydrodynamic coefficients of the heave plate. The hexagonal plate obtains higher damping coefficients compared to other shapes.